Intelligent Load Frequency Control considering Large Scale Photovoltaic Generation. - Awan Uji Krismanto; Herlambang Setiadi (Department of Electrical Engineering, Institut Teknologi Nasional Malang, Indonesia, 2018)
Large-scale renewable energy integration involving large scale PV plant is becoming popular in the last decade due to global warming and climate change. PV plant offers clean and environmentally friendly electricity. However, PV plant also provides unwanted impact in term of frequency stability. Hence appropriate, load frequency control due to the integration of PV plant is inevitable. This paper proposed an intelligent approach based on a differential evolutional algorithm (DEA) to optimize the control parameters of load frequency control (LFC) device. Time domain simulation was carried out to analyses, the frequency nadir of the system. The simulation results suggested that a significant enhancement of system dynamic behavior was monitored when the control parameters of LFC were optimized using the proposed DEA. Moreover, the proposed algorithm provided a promising result to improve system dynamic response in the system with high penetration of PV power plant.